Analisis Variasi Temperatur Aktivasi Terhadap Struktur Kristalin Arang Aktif Dari Tandan Aren (Arenga Pinnata Merr) Dengan Agen Aktivasi Potassium Silicate (K2SiO3) - Nurlia, Nurlia; Anas, Muhammad; Erniwati, Erniwati (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to determine the effect of variations of  activation temperature of  activated carbon from sugar palm bunches of chemically activatied with the activation agent of potassium silicate (K2SiO3) on the crystalline structure. Activated carbon is the result of pyrolysis of carbonaceous raw materials at temperatures lower than  of 1000 oC. Activated carbon from bunches of sugar palm acquired in four steps: preparation steps, carbonization steps using the pyrolysis reactor with temperature of 300 oC - 400 oC for 8 hours and chemical activation using of potassium silicate (K2SiO3) activator in weight ratio of 2: 1 and physical activation using the electric furnace for 30 minutes with temperature variation of 600 oC, 650 oC, 700 oC, 750 oC and 800 oC. The crystalline structure tested by X-Ray Diffraction (XRD) method, the results yielded of 26,60o, 26,62o, 26,16o, 26,22o, 26,97o,  and 26,68o respectively. The highest crystalline structure yield was 22.26% at temperature of  600 oC and the lowest was 8.83% at temperature of 650 oC. The results obtained were amorphous  91.17% at the highest temperature of 650 oC and the lowest 77.74% at temperatur of  600 oC  which has a random and irregular arrangement pattern of atoms or molecules repeatedly or not periodically.